Development of a Proprioceptive Neuromuscular Facilitation Stretching System Using a Low-Speed, High-Torque Motor - Akihiro Azuma; Kazuhiro Matsui; Toshiyuki Kawamura (Asociación Española de Ciencias del Deporte, 2023)
This study aimed to develop a proprioceptive neuromuscular facilitation (PNF) stretching system using a low-speed, high-torque motor and to investigate the acute response in hip flexion range of motion by applying PNF stretching using this system. The PNF stretching system consisted of a low-speed, high-torque motor with a rotational torque of 157 Nm, a braking torque of 1470 Nm, and a rotational speed of 6 degrees/s, a lever arm attached to the motor and its rotating shaft, and a pedestal mounted on the lever arm. The system, which targets hamstrings, enabled the subjects to raise the leg in a supine straight leg raise position and perform passive muscle lengthening and isometric muscle contractions by operating an electric motor. The study included 21 healthy male students aged between 18 and 21 years. The hold-relax (HR) technique was employed, in which the target muscle was lengthened step by step by performing three 10 s isometric contractions. The hip joint flexion angles were measured at the limit of leg raising without discomfort before and after HR (pre-HR and post-HR) and compared using Wilcoxon signed-rank sum test. The results showed that the hip flexion angle at post-HR (81.4 ± 18.0 degrees) was significantly greater than that at pre-HR (63.9 ± 15.2 degrees) (P < 0.05, effect size = 0.88). In conclusion, the PNF stretching system, which uses a low-speed, high-torque motor, effectively leads to an immediate improvement in hamstring flexibility.